Development of gene motif modulation for information processing in artificial DNA computing - Shamsudin, Ahmad Faizul; Suhaimi, Mohd Adam; Ibrahim Ali , Noorbatcha; Hussin, Ummu Salamah; A. F., Alya Khadijah; D., Nor Hidayah (2014)
In the artificial DNA computing model, the MAS (Multi-Agent System) algorithm depicts the sender agent transmits moleware information through the control agent which is then converted to binary data as input to the receiver agent. Gene Motif switching method in the control agent provides the key function for this binary switch and also as an error correcting and redundant modulator. Parity Principles and Hemming code lattice methods are used for Gene Motif binary switching and modulation. The results indicate improvement in the convergence of information decay between artificial and natural systems using the later method. Further development of Gene Motif binary switch in artificial DNA computing may lead to a MAS algorithm that can simulate a natural DNA computing.